2018
DOI: 10.3892/etm.2018.5863
|View full text |Cite
|
Sign up to set email alerts
|

GSK126 (EZH2 inhibitor) interferes with ultraviolet A radiation‑induced photoaging of human skin fibroblast cells

Abstract: Abstract. Polycomb group genes (PcG) encode chromatin modification proteins that are involved in the epigenetic regulation of cell differentiation, proliferation and the aging processes. The key subunit of the PcG complex, enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2), has a central role in a variety of mechanisms, such as the formation of chromatin structure, gene expression regulation and DNA damage. In the present study, ultraviolet A (UVA) was used to radiate human dermal fibroblasts in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Another significant finding of our study was that the silencing of PVT1 or the upregulation of FOXA1 can inhibit the apoptosis and damage of podocytes, while GSK126, an EZH2 inhibitor, can reverse the damage and apoptosis of podocytes in DN. GSK126, a methyltransferase activity inhibitor, has been shown to selectively suppress the activity of EZH2-methyltransferase as well as EZH2 gene expression 20 . It has been reported that PVT1, which is highly expressed in DN podocytes, is induced by HG and is involved in the accumulation of extracellular matrix 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Another significant finding of our study was that the silencing of PVT1 or the upregulation of FOXA1 can inhibit the apoptosis and damage of podocytes, while GSK126, an EZH2 inhibitor, can reverse the damage and apoptosis of podocytes in DN. GSK126, a methyltransferase activity inhibitor, has been shown to selectively suppress the activity of EZH2-methyltransferase as well as EZH2 gene expression 20 . It has been reported that PVT1, which is highly expressed in DN podocytes, is induced by HG and is involved in the accumulation of extracellular matrix 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence is characterized by the oxidative stress that results from the accumulation of ROS and lysosome content [28]. We conducted a CM-H 2 DCFDA staining assay using flow cytometry to assess whether ES-GNPs could effectively inhibit the intracellular ROS production in UVA-irradiated HDFs.…”
Section: Es-gnps Inhibit Ros Production and Lysosome Content In Uva-imentioning
confidence: 99%
“…Photoaging reduces the amount of mature type I collagen and elastic fibers in the dermis of the skin. The clinical characteristics of photoaging occur mainly on exposed skin, such as the face, neck, and forearm, where rough skin, loss of elasticity, deepening and thickening of wrinkles, a leather-like appearance, pigmentation, and dilated capillaries can occur ( Qin et al, 2018 ). Studies have shown that approximately 65% of patients with melanoma and 90% of patients with non-melanoma skin cancers, including BCC and SCC, are associated with skin photoaging ( Damiani and Ullrich, 2016 ).…”
Section: Introductionmentioning
confidence: 99%